The Public’s Awareness of and Attitude Toward Research Biobanks – A Regional German Survey - Bossert, Sabine; Kahrass, Hannes; Strech, Daniel (Frontiers in Genetics, 2018)
Background: Biobanks have become an increasingly important means of biomedical research and innovation. However, they entail a variety of ethical, social and legal challenges, which need to be publicly discussed and managed collectively. A certain level of public awareness of biobank research is an important prerequisite for the public to form an opinion on the issue at hand and to be willing to participate in public engagement activities. For many countries, including Germany, recent information on the public’s awareness of and attitude towards biobanks is scarce. Methods: Therefore, by means of a postal survey in a German urban region, this study updates data from the 2010 Eurobarometer by analysing 1) the public’s awareness of biobanks, 2) their general attitude towards biobanks, and 3) their hypothetical willingness to donate their own biological samples and personal or medical data. Results: Overall, 204 (20.4%) of 998 delivered questionnaires were returned. The majority of survey respondents stated a positive attitude towards medical research (95.5%) and – to a somewhat lower degree – towards genetic research (61.3%). Attitudes towards biobanks were mixed but positive for the majority of respondents: in a question about their spontaneous assessment of biobanks as a means for medical research, 77% showed positive attitudes towards biobanks (36.6 % “definitely” and 40.5% “somewhat positive”). This finding is also reflected in a high proportion of individuals willing to participate in biobank research: 70.4% of respondents would be willing to donate biomaterial to a biobank during a hypothetical stay in hospital. In spite of the high overall support respondents show for biobanks (e.g. positive general attitude and willingness to participate), only about one third (30.8%) had previously heard of biobanks. Discussion and Conclusion: The comparison of survey results with prior data from the 2010 Eurobarometer indicates that public awareness of biobanks remains low. A higher level of biobank awareness can be assumed to be one prerequisite for public engagement in future decisions on biobank governance. We therefore argue that to increase public awareness of biobanks and to enable public involvement in biobank governance, publicly available and understandable information must be provided and disseminated.